Universal Beauty: Analysis of L’Oreal Paris Advertising by Semiotic Charles Sanders Peirce - Abigail Azzahra Ramadhan; Veliana Hardjantini; Tirza Yedida Onasie (Syntax Idea)
This study aims to analyze the universal message conveyed through the emphasized symbols in the advertisement of L'Oreal Paris Infallible Foundation targeting multicultural audiences. In the era of globalization, global beauty brands such as L'Oreal Paris play a significant role in generating product innovations advertised extensively, including through digital platforms. The Charles Sanders Peirce semiotic analysis method is employed to identify signs and symbols in the advertisement and to analyze the universal meanings and messages conveyed. The findings reveal that the advertisement of L'Oreal Paris Infallible Foundation, showcased on the Official YouTube L'Oreal Paris Indonesia, successfully delivers its universal message by embracing diversity through the representation of models with diverse backgrounds. In this context, diversity is not only seen in the variability of skin tones but also in different cultures, races, and ethnicities. L'Oreal Paris effectively conveys the message that beauty is not confined to specific standards; rather, it is perceived as something broad, inclusive, and represented by various shapes and colors. Furthermore, the slogan "you're worth it" implicitly rejects narrow beauty stereotypes and norms, reinforcing the idea that every individual possesses unique and valuable beauty without having to conform to narrow standards. Thus, this advertisement not only promotes beauty products but also conveys a strong message of self-acceptance and appreciation for diversity in beauty perception. The universal message in this advertisement creates a positive and inclusive relationship with multicultural communities. This underscores the importance of understanding and acknowledging cultural diversity and values held by various societal groups in an increasingly interconnected era of globalization. Hence, L'Oreal Paris is deemed successful in promoting its products with an inclusive and culturally relevant approach, making it a good example of expanding market reach positively and effectively